Ketika Iman Bertemu Psikologi Mengurai Dinamika Keyakinan Religius dalam Proses Terapi - Fierly Noer Halida; Devina Hafsah; Wiilda Novia Setiani (CV. Lentera Literasi Indonesia, 2026)
This study is based on the importance of religious beliefs in individual life, particularly in dealing with psychological problems and the process of mental health recovery. In Islamic educational settings, religiosity often forms part of clients’ backgrounds when they receive psychological services, thereby influencing the course of the therapeutic process. This study aims to identify the role of religious beliefs in the process of clinical psychology intervention at the Psychology Service Unit (ULP) of UIN Sunan Gunung Djati Bandung. This study employs a qualitative approach using a case study method. The research subject was a clinical psychologist working at the Psychology Service Unit of UIN Sunan Gunung Djati Bandung, selected through purposive sampling. Data were collected through in-depth interviews and non-participant observation, and then analyzed using descriptive qualitative analysis. The findings indicate that religious beliefs can play a positive role in the therapeutic process when they are interpreted positively by clients, such as helping them feel calmer, increasing patience, and fostering hope in dealing with psychological problems. However, this study also found that rigid religious understanding and spiritual conflicts can become obstacles in the therapy process. Therefore, the integration of religious aspects into psychological services needs to be carried out wisely and adjusted to the clients’ conditions. This study concludes that religiosity plays different roles for each individual and needs to be understood contextually in psychological services within Islamic educational environments.